2009
DOI: 10.1016/j.neuroimage.2008.10.020
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of D2/D3 receptor binding in the adolescent rhesus monkey using small animal PET imaging

Abstract: PET imaging of the neuroreceptor systems in the brain has earned a prominent role in studying normal development, neuropsychiatric illness and developing targeted drugs. The dopaminergic system is of particular interest due to its role in the development of cognitive function and mood as well as its suspected involvement in neuropsychiatric illness. Nonhuman primate animal models provide a valuable resource for relating neurochemical changes to behavior. To facilitate comparison within and between primate mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…This is consistent with the lack of sex differences seen in striatal D 2 /D 3 receptor binding using [ 18 F]-fallypride in adolescent rhesus monkeys (Christian et al 2009) and with previous reports of women and men showing equivalent D2-like receptor availability (Farde et al 1995; Pohjalainen et al 1998; Munro et al 2006). However, it has been suggested that female sex hormones may enhance presynaptic dopamine turnover (Laakso et al 2002), and the radiotracer used in this experiment (FCP) is sensitive to fluctuations in menstrual cycle phase (Czoty et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the lack of sex differences seen in striatal D 2 /D 3 receptor binding using [ 18 F]-fallypride in adolescent rhesus monkeys (Christian et al 2009) and with previous reports of women and men showing equivalent D2-like receptor availability (Farde et al 1995; Pohjalainen et al 1998; Munro et al 2006). However, it has been suggested that female sex hormones may enhance presynaptic dopamine turnover (Laakso et al 2002), and the radiotracer used in this experiment (FCP) is sensitive to fluctuations in menstrual cycle phase (Czoty et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the DVR in the high 5-HTT binding regions of the s-carrier group revealed a larger variance, which is attributed to a smaller sample size. Because the mean DVRs between genotype groups are approximately the same, we believe that it is unlikely that a larger sample size would reveal group differences, given typical intersubject variations of 10%–20% in PET neuroreceptor studies (Christian et al, 2009; Costes et al, 2005; Ito et al, 2008; Rabiner et al, 2002). …”
Section: Discussionmentioning
confidence: 96%
“…Across a cohort of animals with variable levels of cerebellar binding, this will result in high variability of BP ND estimation in low-receptor-density regions such as the cortex. We have recently reported high variability in cortical 18 F-fallypride binding (in BP ND ) in a large cohort of rhesus monkeys (Christian et al , 2009), which may be a direct consequence of cohort variation in cerebellar D 2 /D 3 receptor concentration. The extent and variability of D 2 /D 3 density in the cerebellum (lobes) in the population is not known, and thus it is not possible to assess the variability in BP ND due to cerebellar specific binding.…”
Section: Discussionmentioning
confidence: 98%